Cardiovascular Dysfunction in COVID-19: Association Between Endothelial Cell Injury and Lactate - Yang, Kun; Holt, Matthew; Fan, Min; Lam, Victor; Yang, Yong; Ha, Tuanzhu; Williams, David L.; Li, Chuanfu; Wang, Xiaohui (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19), an infectious respiratory disease propagated by a new virus known as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), has resulted in global healthcare crises. Emerging evidence from patients with COVID-19 suggests that endothelial cell damage plays a central role in COVID-19 pathogenesis and could be a major contributor to the severity and mortality of COVID-19. Like other infectious diseases, the pathogenesis of COVID-19 is closely associated with metabolic processes. Lactate, a potential biomarker in COVID-19, has recently been shown to mediate endothelial barrier dysfunction. In this review, we provide an overview of cardiovascular injuries and metabolic alterations caused by SARS-CoV-2 infection. We also propose that lactate plays a potential role in COVID-19-driven endothelial cell injury.